Palmatine treats urticaria by reducing inflammation and increasing autophagy - Xiao, Tian; Yu, Xingzhi; Yang, Liping; Duan, Xiaohua (Frontiers in Immunology, 2023)
Introduction Chronic spontaneous urticaria (CSU) is mainly manifested as wheals and erythema on the skin accompanied by itching, which will cause emotional anxiety and seriously affect the quality of life in patients. Palmatine (PAL) is a main chemical component of Yajieshaba, which has been found to effectively alleviate the symptoms of food allergy. However, its role and mechanism in CSU remain unclear. The present study aimed to investigate the protective effect of PAL on CSU rats. Methods We replicated the CSU rat model by intraperitoneal injection of ovalbumin (OVA) in rats on days 0, 2, 4, and 14, with a double dose given on the last challenge. PAL, loratadine and saline were given by gavage from day 5 to day 14. We observed the skin pathologic changes, mast cell degranulation, immune factor levels, inflammatory response and autophagy-related protein expression in CSU rats. Results We found PAL treatment to be effective in alleviating CSU-like skin lesions and reducing itching and mast cell degranulation in rats. Compared with the OVA group, the levels of immune and inflammatory factors were significantly reduced, neutrophil recruitment was alleviated, suggesting a reduced inflammatory response. The autophagy results showed that PAL further increased the expression of LC3, Beclin-1 and p-LKB1, p-AMPK, Atg5, Atg12 and Atg5-Atg12, while P62 and p-p70S6K1 expression decreased. They collectively suggested that autophagic flux was activated after PAL treatment. However, there was an increase in the expression of LC3I, probably due to the fact that PAL induced its accumulation in order to provide substrate for the generation of more LC3II. Discussion Overall, PAL had a protective effect on CSU in normal rats, activated the expression of autophagy and improved the inflammatory response.